Prolactin regulates luminal bicarbonate secretion in the intestine of the sea bream (Sparus aurata L.) - Ferlazzo, A. (2012)
The pituitary hormone prolactin is a pleiotropic endocrine factor that plays a major role in the regulation of ion balance in fish, with demonstrated actions mainly in the gills and kidney. The role of prolactin in intestinal ion transport remains little studied. In marine fish, which have high drinking rates, epithelial bicarbonate secretion in the intestine produces luminal carbonate aggregates believed to play a key role in water and ion homeostasis. The present study was designed to establish the putative role of prolactin in the regulation of intestinal bicarbonate secretion in a marine fish. Basolateral addition of prolactin to the anterior intestine of sea bream mounted in Ussing chambers caused a rapid (<20min) decrease of bicarbonate secretion measured by pH-stat. A clear inhibitory dose–response curve was obtained, with a maximal inhibition of 60–65% of basal bicarbonate secretion. The threshold concentration of prolactin for a significant effect on bicarbonate secretion was 10ngml–1, which is comparable with putative plasma levels in seawater fish. The effect of prolactin on apical bicarbonate secretion was independent of the generation route for bicarbonate, as shown in a preparation devoid of basolateral HCO3 –/CO2 buffer. Specific inhibitors of JAK2 (AG-490, 50mmoll–1), PI3K (LY-294002, 75mmoll–1) or MEK (U-012610, 10mmoll–1) caused a 50–70% reduction in the effect of prolactin on bicarbonate secretion, and demonstrated the involvement of prolactin receptors. In addition to rapid effects, prolactin has actions at the genomic level. Incubation of intestinal explants of anterior intestine of the sea bream in vitro for 3h demonstrated a specific effect of prolactin on the expression of the Slc4a4A Na+–HCO3– co-transporter, but not on the Slc26a6A or Slc26a3B Cl–/HCO3 – exchanger. We propose a new role for prolactin in the regulation of bicarbonate secretion, an essential function for ion/water homeostasis in the intestine of marine fish.